GRAMMATICAL ANALYSIS OF “ONE STOP ENGLISH LEARNING” TEXTBOOK GRADE 6 - Khoirun Nikmah; Ayu Fitrianingsih; Dian Ratna Puspananda (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
An English textbook is needed by the learners to study the materials presented by the teacher or learn independently. A textbook must contain fewer errors, especially in grammar, because they can confuse the students and influence the outcome of their learning process. This descriptive quantitative research is aimed at investigating the types of grammatical errors and determining whether the book is applicable or not for teaching sixth-grade students. The grammar inside the book was analyzed by Depraetere and Langford as well as Azar's theories. The data sources were derived from the sixth-grade elementary school textbook entitled "One Stop English Learning", which was published by Edutama Mulia in 2018 and written by Bashori Alwi. This book has been widely used by elementary schools in rural and urban areas. The researchers found 6 grammatical errors in unit 1, and 1 error in unit 2. Those errors were related to tenses, plural nouns, and subject-verb agreement. Since the grammatical errors in this book were less than 50%, the book is still considered good enough to be used as a learning source. However, teachers and students must be more careful with these small errors.